The Effectiveness of Discovery-Based Virtual Laboratory Learning to Improve Student Science Process Skills - Nirmala, W.; Darmawati, S. (Journal of Education Technology, 2021)
The inadequate condition of the laboratory, facilities, and infrastructure is the main obstacle to the lack of practicum activities. The purpose of this study was to examine the effectiveness of discovery-based virtual laboratory learning in improving science process skills of students. This type of research is a one-group-pretest-postest design research. Population and sample taken were students who took Basic Chemistry II course. The data collection method was carried out in a documentary manner and data analysis was in the form of calculating the percentage increase in science process skills and the criteria for the effectiveness of N-Gain. The results obtained were discovery-based virtual laboratory learning that succeeded in improving students' science process skills. Science process skills with high criteria increased by 91% and in the moderate category by 9%. Based on the N-Gain calculation, discovery-based virtual laboratory learning obtained an average percentage of effectiveness of 66% so it can be concluded that discovery-based virtual laboratory learning is quite effective in improving student science process skills. Through discovery-based virtual laboratory learning, student science process skills are more easily developed so that learning becomes more meaningful.